Partisipasi Masyarakat dalam Pengelolaan Sampah pada Kawasan Wisata Pantai - Titi Darmi; Meta Aryanti (JOPPAS: Journal of Public Policy and Administration Silampari, 2022)
The purpose of this study was to determine community participation in waste management in the coastal tourism area of Bengkulu City. The research method is qualitative by using descriptive methods. Data and informants as many as six people with data collection techniques namely observation, interviews, and documentation. The results showed that there was community participation in waste management on the coast of Bengkulu City. Community participation is influenced by three main things, namely the willingness, ability, and opportunity of the community to participate. There is still a need for improvement from the community to be able to participate in waste management and the lack of waste infrastructure in coastal areas which affects waste dumped carelessly. The conclusion of this study is that the community has begun to be aware and is trying to participate in reducing waste in coastal tourism areas in Bengkulu City, but there is still a need for additions, repairs or replacement of infrastructure that is no longer suitable for use at several coastal points. Keywords: Community Participation, Waste Management